Scalable, Lightweight, Integrated and Quick-to-Assemble (SLIQ) Hyperdrives for Functional Circuit Dissection - Liang, Li; Oline, Stefan N.; Kirk, Justin C.; Schmitt, Lukas Ian; Komorowski, Robert W.; Remondes, Miguel; Halassa, Michael M. (Frontiers in Neural Circuits, 2017)
Independently adjustable multielectrode arrays are routinely used to interrogate neuronal circuit function, enabling chronic in vivo monitoring of neuronal ensembles in freely behaving animals at a single-cell, single spike resolution. Despite the importance of this approach, its widespread use is limited by highly specialized design and fabrication methods. To address this, we have developed a Scalable, Lightweight, Integrated and Quick-to-assemble (SLIQ) multielectrode array platform. This platform additionally integrates optical fibers with independently adjustable electrodes to allow simultaneous single unit recordings and circuit-specific optogenetic targeting and/or manipulation. In current designs, the fully assembled platforms are scalable from two to thirty-two microdrives, and yet range one to three grams, light enough for small animals. Here, we describe the design process starting from intent in computer-aided design (CAD), parameter testing through finite element analysis and experimental means, and implementation of various applications across mice and rats. Combined, our methods may expand the utility of multielectrode recordings and their continued integration with other tools enabling functional dissection of intact neural circuits.